Seroprevalence of Cytomegalovirus among Pregnant Women Attending Murtala Muhammad Specialist Hospital, Kano - Surajo Jibrin3, Ahmad Saleh*1, Lawal Dahiru Rogo2, Isah Abubakar Aliyu2, Jamilu Abubakar Bala2, Aminu Ibrahim2 and Muhammad Salihu Baba 4 (Sokoto Journal of Medical Laboratory Science)
Cytomegalovirus (CMV) infection is a common cause of miscarriage, growth retardation and congenital infections in pregnancy. This congenital infection can cause serious disease to the foetus such as blindness and deafness. This study determined the seropositivity of cytomegalovirus among pregnant women attending the Antenatal Clinic of Murtala Muhammad Specialist Hospital Kano. The total number of the subjects recruited for this study was 91 pregnant women and blood sample were taken from each subject. Demographic data was obtained using a pre-designed questionnaire. The samples were assayed for cytomegalovirus IgG antibody using ELISA kit. Data obtained were analyzed using SPSS version 20 using descriptive statistics, Chi-square test logistic regression at 0.05 significance level. Seventeen (79) samples out of the 91 tested positive, giving a prevalence of 86.8%. The positivity of cytomegalovirus was found to be higher among age group 26 – 30 with a prevalence of (35.4%) and the least CMV seroprevalence, of (5.1%) was found in the pregnant women in the age range 40– 45 years. This study established no significant relationship between seropositivity of CMV and history of blood transfusion and also handling of children with deformity. This study has provided evidence of CMV infection circulation among pregnant women in the study area and therefore should be considered important in the screening and management of pregnancy to avoid the lethal effects of the virus on the foetus.